1996
DOI: 10.1164/ajrccm.153.1.8542162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of overnight supplemental oxygen in obstructive sleep apnea in children.

Abstract: Supplemental oxygen during sleep may be useful as a temporary palliative treatment in children with obstructive sleep apnea syndrome (OSAS) associated with significant hypoxemia. However, supplemental O2 may also blunt hypoxic ventilatory drive and worsen ventilation. To assess the safety of the use of supplemental O2 in children with OSAS, we studied 16 children ages 2-8 (mean: 4.28 +/- 2.88 yr) with OSAS secondary to adenotonsillar hypertrophy. Patients underwent two overnight polysomnograms within 1 mo, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
9

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 18 publications
0
15
0
9
Order By: Relevance
“…In our study, children with severe SDB also scored significantly lower than the other children with less severity on the attention domain. One possible cause was that SDB leads to decreased arterial blood oxygen saturation, and results in hypoxemia in the brain [41]. A potentially serious consequence of intermittent hypoxia during sleep might involve its long-term effects on neuronal function [42].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, children with severe SDB also scored significantly lower than the other children with less severity on the attention domain. One possible cause was that SDB leads to decreased arterial blood oxygen saturation, and results in hypoxemia in the brain [41]. A potentially serious consequence of intermittent hypoxia during sleep might involve its long-term effects on neuronal function [42].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the significant highness of preoperative psychiatric disorders and symptoms in patients who were decided with surgery indication as a result of the parent anamnesis and physical examination and similar levels of these symptoms and disorders with those of the control group in the postoperative month six, support the aforementioned data. Because previous studies reported that more than half of patients with an indication of adenotonsillectomy based on anamnesis and a physical examination had OSA(À) (31-54%) [55][56][57]. Our patient group consisted of preschool children aged three to five years.…”
Section: Discussionmentioning
confidence: 99%
“…Er is weinig bekend over de mechanismen waarop zuurstoftherapie bij OSAS werkzaam is en er bestaat onduidelijkheid over de effectiviteit van de behandeling. De behandeling leidt wel tot een zuurstofstijging in het bloed, maar verlaagt de AHI niet of nauwelijks Aljadeff et al, 1996).…”
Section: Zuurstoftherapieunclassified